2012
DOI: 10.1002/cne.22797
|View full text |Cite
|
Sign up to set email alerts
|

Planar multipolar cells in the cochlear nucleus project to medial olivocochlear neurons in mouse

Abstract: Medial olivocochlear (MOC) neurons originate in the superior olivary complex and project to the cochlea, where they act to reduce the effects of noise masking and protect the cochlea from damage. MOC neurons respond to sound via a reflex pathway, however, in this pathway the cochlear nucleus cell type that provides input to MOC neurons is not known. We investigated whether multipolar cells of the ventral cochlear nucleus have projections to MOC neurons, by labeling them with injections into the dorsal cochlear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 42 publications
2
43
0
1
Order By: Relevance
“…The greater DPOAE suppression found in subject groups with tinnitus and/or low SLT (relative to no tinnitus, high SLT) indicates a net hyperresponsiveness of the portion of the MOC system activated by noise stimulation in the present experiments. The exact basis for the measured hyperresponsiveness is unclear but may involve the following: 1) increased responsiveness of MOC interneurons, that is, planar multipolar cells (T stellate cells) of the PVCN, which receive auditorynerve input from the noise-stimulated ear and provide excitatory input to MOC neurons, which are located in the superior olivary complex (Darrow et al 2012); 2) increased responsiveness of MOC neurons themselves, as might be mediated by the large, presumably excitatory endings onto these cells that may represent descending inputs from auditory cortex (Brown et al 2013), 3) increased efficacy of any or all of the synapses in the chain of MOC feedback to the DPOAE-recorded cochlea, including between MOC terminals and outer hair cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater DPOAE suppression found in subject groups with tinnitus and/or low SLT (relative to no tinnitus, high SLT) indicates a net hyperresponsiveness of the portion of the MOC system activated by noise stimulation in the present experiments. The exact basis for the measured hyperresponsiveness is unclear but may involve the following: 1) increased responsiveness of MOC interneurons, that is, planar multipolar cells (T stellate cells) of the PVCN, which receive auditorynerve input from the noise-stimulated ear and provide excitatory input to MOC neurons, which are located in the superior olivary complex (Darrow et al 2012); 2) increased responsiveness of MOC neurons themselves, as might be mediated by the large, presumably excitatory endings onto these cells that may represent descending inputs from auditory cortex (Brown et al 2013), 3) increased efficacy of any or all of the synapses in the chain of MOC feedback to the DPOAE-recorded cochlea, including between MOC terminals and outer hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to the proposal of a spontaneously hyperactive MOC system are animal data indicating the development of elevated spontaneous activity in ventral cochlear nucleus unit types following acoustic trauma, a known inducer of tinnitus (Vogler et al 2011). The elevated activity that develops in onset choppers and transient choppers has particular relevance because there is evidence that both of these unit types (or subgroups thereof) are part of the MOC system, either projecting to MOC neurons (transient choppers, which correspond to T stellate cells) or receiving MOC input (both onset and transient choppers; Darrow et al 2012;Mulders et al 2007;Oertel et al 2011). These animal data demonstrate that hyperactivity can indeed develop within certain elements of the MOC system.…”
Section: Discussionmentioning
confidence: 99%
“…That is because these neurons receive another terminal type (with Sm Rnd vesicles) that is also presumably excitatory but that is not associated with spines. Those terminals are likely to originate in the cochlear nucleus, in multipolar cells that project to MOC neurons and drive their excitatory response to sound (Thompson and Thompson, 1991a,1999b; de Venecia et al, 2005; Darrow et al 2012). Thus, the terminals with Lg Rnd vesicles are likely to modulate the reflexive response to sound, and they may originate in descending inputs to MOC neurons from the inferior colliculus (Vetter et al, 1993) or auditory cortex (Mulders and Robertson, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…We found that at least half of these cells are planar cells. Projections of MOC neurons from this cell type have been shown by independent experiments using anterograde tracing of dextran aminelabeled axons (Darrow et al 2012 (Godfrey et al 1975;Robertson 1984;Liberman and Brown 1986).…”
Section: Cochlear Nucleus Cell Types Providing Inputs To Oc Neuronsmentioning
confidence: 88%
“…CN transneuronal labeling is found in multipolar cells (Horvath et al 2003), but the labeled subtype within this heterogeneous class (reviewed by Doucet and Ryugo 2006) was not identified. Recent work using conventional tracers suggests that one class, planar multipolar cells, projects to MOC neurons (Darrow et al 2012), and we examine here whether they and other subtypes are transneuronally labeled. We also examine whether the two types of IC neurons, cells with disc-shaped dendritic fields and cells of stellate shape, are transneuronally labeled.…”
Section: Introductionmentioning
confidence: 99%